Students with Special Educational Needs in the Education Process - Haskaj A.; Chichevska Jovanova, Natasha (Faculty of Philosophy, University of Tetova, Republic of Macedonia, 2020)
The cooperation of the school with parents begins in the early years of schooling and accompanies the student throughout their school experience. The purpose of this research is to analyze the impact of different characteristics of parents and teachers on the involvement of parents in the educational process of their children. The research included 142 teachers of students aged 6 to 15 years, i.e. students from I-IX grades, and 115 parents of children with typical development and parents of children with special educational needs. According to the research, students with special educational needs should study in special elementary schools, the academic performance of children with special educational needs is better in special elementary schools, compared to children who study in regular schools. Both teachers and parents should have good cooperation, make efforts to get the best of children with special educational needs, no matter if they study in special elementary school or regular school.
Keywords: parents, teachers, school, student, cooperation